Brushing the distal biliary stricture in the surrounding of the papilla increased the risk of post-endoscopic retrograde cholangiopancreatography pancreatitis: A retrospective study using propensity score analysis. Issue 7 (November 2017) - Kato, Kunihiro; Sugimori, Satoshi; Kakiya, Yuki; Maruyama, Hirotsugu; Fukunaga, Shusei; Nagami, Yasuaki; Shiba, Masatsugu; Tanigawa, Tetsuya; Watanabe, Toshio; Fujiwara, Yasuhiro
Background and aims: Brushing cytology is useful for diagnosing biliary strictures. With regard to biliary stricture brushing at the distal common bile duct in the surrounding of the papilla, the risk of post-endoscopic retrograde cholangiopancreatography pancreatitis is unknown. Our study aimed to evaluate the risk of post-endoscopic retrograde cholangiopancreatography pancreatitis by using this procedure. Methods: A total of 150 endoscopic retrograde cholangiopancreatography-naïve patients undergoing endoscopic retrograde cholangiopancreatography including biliary stricture brushing were retrospectively analyzed. Patients were divided into two groups: the surrounding of the papilla group ( n  = 25) and the other group ( n  = 125). The primary outcome was the post-endoscopic retrograde cholangiopancreatography pancreatitis incidence. We analyzed the risk of post-endoscopic retrograde cholangiopancreatography pancreatitis by using inverse probability of treatment weighting based on propensity scores to adjust for selection bias. Results: The overall incidence of post-endoscopic retrograde cholangiopancreatography pancreatitis was 11.3%, and post-endoscopic retrograde cholangiopancreatography pancreatitis of the surrounding of the papilla group occurred significantly more frequently than in the other group (32.0% vs 7.2%, p  < 0.01). Multivariate analysis showed that this procedure was a risk factor for post-endoscopic retrograde cholangiopancreatography pancreatitis (odds ratio, 10.6; 95% confidence interval, 2.82–40.2; p  < 0.01). In the propensity-weighted model, this procedure was an independent risk factor for post-endoscopic retrograde cholangiopancreatography pancreatitis (odds ratio, 8.42; 95% confidence interval, 2.12–32.4; p  < 0.01) by multivariate analysis. Conclusions: Biliary stricture brushing at the distal common bile duct in the surrounding of the papilla may increase the risk of post-endoscopic retrograde cholangiopancreatography pancreatitis compared with brushing other portions.